Global and Site-Specific Changes in 5-Methylcytosine and 5-Hydroxymethylcytosine after Extended Post-mortem Interval - Gross, Jeffrey A.; Nagy, Corina; Lin, Li; Bonneil, Éric; Maheu, Marissa; Thibault, Pierre; Mechawar, Naguib; Jin, Peng; Turecki, Gustavo (Frontiers in Genetics, 2016)
There has been a growing interest in the study of epigenetic mechanisms to elucidate the molecular bases of human brain-related diseases and disorders. Frequently, researchers utilize post-mortem tissue with the assumption that post-mortem tissue decay has little or no effect on epigenetic marks. Although previous studies show no effect of post-mortem interval on certain epigenetic marks, no such research has been performed on cytosine modifications. In this study, we use DNA from the brains of adult Sprague Dawley rats subjected to post-mortem intervals at room temperature, ranging from 0 to 96 h, to assess the stability of cytosine modifications, namely 5-methycytosine and 5-hydroxymethylcytosine. Our results indicate that neither global nor site-specific levels of 5-methycytosine and 5-hydroxymethylcytosine are affected by the post-mortem intervals we studied. As such, the use of post-mortem tissue to study cytosine modifications in the context of neurological or neuropsychiatric disorders is appropriate.